2000
DOI: 10.1029/2000jd900071
|View full text |Cite
|
Sign up to set email alerts
|

Reactive uptake of ozone by proxies for organic aerosols: Surface versus bulk processes

Abstract: Abstract. Uptake measurements of ozone were conducted with two types of proxies for atmospheric organic aerosols: organic liquids and self-assembled organic monolayers. Alkanes and terminal alkenes were used. The monolayer surface was characterized, prior to and after reaction, using IR spectroscopy. Uptake experiments were conducted using a flow tube reactor coupled to a chemical ionization mass spectrometer. The reactive uptake coefficient, ¾, is shown to be due to reaction with the double bond. For the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
215
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(231 citation statements)
references
References 57 publications
11
215
5
Order By: Relevance
“…49,53,54 However, our measured reactive uptake coefficient was a factor of 10 lower than the measurements made on TASAMs by Moise and Rudich. 49 One explanation for this difference may be that the oleate double bond lies in the center of the molecule and is therefore likely to be less accessible than in the TASAMs. Furthermore, the aqueous nature of our surface and high partial pressures of water may further inhibit the reaction.…”
Section: Results Andcontrasting
confidence: 73%
See 1 more Smart Citation
“…49,53,54 However, our measured reactive uptake coefficient was a factor of 10 lower than the measurements made on TASAMs by Moise and Rudich. 49 One explanation for this difference may be that the oleate double bond lies in the center of the molecule and is therefore likely to be less accessible than in the TASAMs. Furthermore, the aqueous nature of our surface and high partial pressures of water may further inhibit the reaction.…”
Section: Results Andcontrasting
confidence: 73%
“…The reaction has been studied using pure oleic acid aerosols, [37][38][39][40][41][42][43][44][45] 2-30 nm thick films on polystyrene beads, 46 ∼1 µm thick films on aqueous sea salt aerosol 47 and on macroscopic films in coated wall flow tube studies. [48][49][50][51][52] Both volatile and involatile products of oleic acid ozonolysis have been identified, including nonanaldehyde, nonanoic acid, 9-oxononanoic acid, and azelaic acid. 38,46,48 It has also been suggested that ozonolysis may lead to polymerization in pure oleic acid particles 41,42 and for other unsaturated organics in self-assembled monolayers 53,54 and thin films.…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced reaction probability for the surface reaction is consistent with the fact that the terminal double bond should be the part of the SAM that OH first encounters in the structured monolayer, as also proposed for the NO 3 reaction, 57 and with previous studies showing enhanced reactivity at interfaces compared to the gas phase. [19][20][21][22][23][24][25][26][27][28] Reaction on every collision has also been observed for the reaction of Cl atoms with a C3Q SAM. 22 Although there are a number of studies of the OH oxidation of organics on surfaces and in or on particles, there are 25 measured g = 0.29 for the same surface, indicating that even for saturated alkyl chains, the surface reaction is fast.…”
Section: Kineticsmentioning
confidence: 79%
“…39,41,42,71 It is likely that the initial splitting of POZ occurs with nearly equal probability for the formaldehyde and sebaldehydic acid channels. Indeed, (II) and (VIII) are generated in comparable amounts in the oxidized film.…”
Section: Discussionmentioning
confidence: 99%
“…21,[60][61][62] Oxidation of unsaturated fatty acids by ozone has been studied by many researchers. 40,42,44,[63][64][65][66][67][68] Related reactions of ozone with ordered Langmuir films of phospholipids on water 45,46,69 or with unsaturated SAM (self-assembled monolayers) 39,41,[70][71][72][73] have also been examined. As a result, both the gas-phase and surface products of ozonolysis of unsaturated fatty acids are relatively well understood.…”
Section: Introductionmentioning
confidence: 99%